JWH-018 impairs sensorimotor functions in mice. (6th August 2015) - Ossato, A.; Vigolo, A.; Trapella, C.; Seri, C.; Rimondo, C.; Serpelloni, G.; Marti, M.
Highlights: JWH-018 impairs sensorimotor responses in mice by stimulation of CB1 receptors. JWH-018 reduces more powerfully than Δ 9 -THC sensorimotor functions in mice. JWH-018 induces convulsion, myoclonia and hyperreflexia. Abstract: Naphthalen-1-yl-(1-pentylindol-3-yl)methanone (JWH-018) is a synthetic cannabinoid agonist illegally marketed in "Spice" and "herbal blend" for its psychoactive effect greater than those produced by cannabis. In rodents JWH-018 reproduces typical effects of (−)-Δ 9 -THC or Dronabinol® (Δ 9 -THC) such as hypothermia, analgesia, hypolocomotion and akinesia, while its effects on sensorimotor functions are still unknown. Therefore, the aim of the present study is to investigate the effect of acute administration of JWH-018 (0.01–6 mg/kg i.p.) on sensorimotor functions in male CD-1 mice and to compare its effects with those caused by the administration of Δ 9 -THC (0.01–6 mg/kg i.p.). A specific battery of behavioral tests were adopted to investigate effects of cannabinoid agonists on sensorimotor functions (visual, auditory, tactile) and neurological changes (convulsion, myoclonia, hyperreflexia) while video-tracking analysis was used to study spontaneous locomotion. JWH-018 administration inhibited sensorimotor responses at lower doses (0.01–0.1 mg/kg), reduced spontaneous locomotion at intermediate/high doses (1–6 mg/kg) and induced convulsions, myoclonia and hyperreflexia at high doses (6 mg/kg). Similarly, administration of Δ 9 -THC reduced sensorimotor responses in mice but it did not inhibit spontaneous locomotion and it did not induce neurological alterations. All behavioral effects and neurological alterations were prevented by the administration of the selective CB1 receptor antagonist/inverse agonist 1-(2, 4-dichlorophenyl)-5-(4-iodophenyl)-4-methyl-N-(piperidin-1-yl)-1H-pyrazole-3-carboxamide (AM 251). For the first time these data demonstrate that JWH-018 impairs sensorimotor responses in mice. This aspect should be carefully evaluated to better understand the potential danger that JWH-018 may pose to public health, with particular reference to decreased performance in driving and hazardous works.